A Study of the Motion Response of Floating Solar PV and Cross-Flow Savonius Turbine in Moored Conditions - Ramsy de Fretes Patrick; Izzuddin Jifaturrohman Mohammad; Putranto Teguh; Aria Pria Utama I Ketut; Huang Luofeng (BIO Web of Conferences)
The transition towards Net Zero Emissions (NZEs) is being accelerated by hybrid renewable technologies such as Floating Photovoltaic (FPV) systems and marine current turbines, which combine solar panels and cross-flow marine turbines mounted on floating structures for near-shore applications. Despite their innovative potential, these renewable technologies face significant challenges in stability and durability due to the effects of wind, waves, and ocean currents. Therefore, a flexible mooring system is essential to address these challenges. This research examines the influence of variations in the number of mooring lines and wave direction on the hydrodynamic response of FPV systems. Utilizing a catenary mooring system consisting of anchors, mooring lines, floats, and connectors, the study evaluates various configurations to determine the optimal solution for enhanced motion stability. Computational Fluid Dynamics (CFD) simulations are employed to analyze the dynamic response of FPV systems under different environmental conditions, represented on a sea-state scale, with a focus on pure oscillatory motions: heave, roll, and pitch. The findings aim to provide valuable insights for the design and operation of more stable and efficient FPV systems in marine environments, thereby supporting the advancement of sustainable renewable energy.